System of three-dimensional human face images formation for plastic and reconstructive medicine - Аврунін, О. Г.; Носова, Я. В.; Шушляпіна, Н. О. (My University, 2021)
Improving the methods and means of computer planning of functional and aesthetic interventions on the human face based on realistic 3D visualization methods is an urgent task of modern biomedical engineering. Despite a suf-ficient amount of work in the field of medical imaging and image processing, a more accurate and realistic presentation of data is needed for imaging systems aimed at modifying the initial data to predict the results of surgery. Software for 3D visualization in computer modeling of functional and aesthetic surgical interventions should ensure the solution of the following set of tasks: initial computer processing of tomographic data and 3D surface scanning data; selection of a visualization window and tone mapping; segmentation of anatomical structures on tomographic images; determination of the contours of segmented objects on tomographic images; construction and visualization of polygonal models of the anatomical structures of the investigated area.
Keywords: Tomographic Images; Surface Scanning; Visualization